Trajetória, processo formativo e saberes docentes : estudo autobiográfico sobre memórias e ressignificações de um formador de professores na área de ciências naturais - Castro, Edward Bertholine de (2019)
This is an autobiographical study of the formative process of a university professor, in which, episodes and events occurred in the period from 1960 to 2010, configure elements of analysis, as a way to characterize, reflexively, at the macro, meso and micro levels, processes of individual and social subjectivation. I start from the understanding that training, for the exercise of teaching, is a continuous process that requires expansion in the perception of training spaces. I began by covering the panorama of my school and academic education in the late 1960s, in which I consider some personal conflicts, experienced in this period, as formative elements of the I citizen. In the analysis of the events and episodes, I defined the research for the training of teachers and trainers of Nature Sciences of the final years of elementary school and Biology for medical education in Higher Education. I choose qualitative research as a methodological experience using documentary research understood as various forms of registration, in addition to different images composing the autobiography, primary source of information. The registration of memories is used to complement the literature search, and allowed deepening in the analysis with greater objectivity. From the 1970s to the 1990s I contemplate my initial and continuing education and establish interlocutions with my experience and experience in teaching and university management, as well as research and intervention projects, in the areas of teaching and learning in Natural Sciences and Biology. Episodes of experience in union struggles and the organization of social groups in search of theoretical and methodological reflections in addition to scientific technical knowledge were not neglected. In this exercise, I perceived the University as a privileged space that allowed me to exercise critical reflections on reality, in addition to providing me moments of knowledge creation, with scientific bases, perceiving learning as an exercise of research and acquisition of knowledge beyond those technical / professional. In this research, through the reflective narrative of the trajectory of my I, of my formative process and of construction and acquisition of my teaching knowledge, I realize that the autobiography allows the reader to understand the formative process of a teacher trainer as systemic, scientific, creative, collaborative and interdependent and, above all, political, as I understand (at least I try) in the complexity of Being a Teacher, Human Teacher.